Desconcierto del Banco de la República - Sarmiento, Eduardo (Diario El Espectador, 2011)
El viernes pasado el Banco de la República elevó la tasa de interés de referencia a 4%. El mismo día el ministro de Hacienda salió con el gerente del Banco de la República ilustrando las bondades de la medida, y el día siguiente apareció con el presidente de la República diciendo que la tasa no debe subir más.

Last Friday the Bank of the Republic raised the interest rate of reference to 4%. The same day the Minister of Finance went out with the manager of the Bank of the Republic illustrating the benefits of the measure, and the day next appeared with the President of the Republic saying that the rate did not should go up more.
Keywords: Economía - Colombia; Banco de la República - Aspectos económicos - Colombia; Política económica - Colombia; Política monetaria - Colombia; Economy - Colombia; Banco de la República - Economic aspects - Colombia; Economic policy - Colombia; Monetary policy - Colombia